A preliminary study on the classification of pediatric renal artery variations based on the computer-assisted surgical system - SHEN Jiaqi, XIA Nan, XU Ning, WANG Feifei, DONG Qian, HAO Xiwei (精准医学杂志)
Objective To investigate the status and classification of pediatric renal artery variations using the Hisense CAS computer-assisted surgery system. Methods Lower abdominal contrast-enhanced CT images were collected from the children with non-kidney disease or healthy children in The Affiliated Hospital of Qingdao University from January 2013 to December 2024, and the images were imported into the Hisense CAS system to perform three-dimensional reconstruction and construct the model of the kidney. The status and classification of pediatric renal artery variations were summarized and analyzed. Results Left renal artery variations accounted for 10.78%, while right renal artery variations accounted for 10.28%, with no significant difference between the two sides (P>0.05). There were four types of renal artery variations, i.e., prehilar renal artery branch type (type Ⅰ), accessory renal artery type (type Ⅱ), hilar accessory artery type (type Ⅲ), and mixed type (type Ⅳ), accounting for 16.79%, 5.76%, 3.01%, and 0.50%, respectively. Conclusion The model of the kidney constructed based on the Hisense CAS system can clearly show the shape of the renal artery and clarify the type of renal artery variation, which provides an anatomical basis for the preoperative planning of renal surgery and a reference for subsequent research.